Utilizing an End-User Driven Process to Identify and Address Climate-Resilience Tool Needs in the U.S. Gulf of Mexico. Issue 2 (14th March 2022) - Collini, Renee C.; Heming, Mikaela C.; Mohrman, Christina; Daigle, Melissa T.; Fulford, Casey A.; Lowry, Celina L. Gauthier; Hanisko, Marian D.; Mikulencak, Steven; Price, Rhonda; Ransom, Kristin R.; Sempier, Tracie T.; Shepard, Christine; et al.
Abstract: Many tools have been generated in recent decades to support decision-makers in understanding and acting on climate science, causing stakeholders in the Gulf of Mexico (Gulf) to repeatedly express the need for guidance when selecting climate resilience tools. The Climate and Resilience Community of Practice (CoP), Gulf of Mexico Alliance (GOMA), and the Northern Gulf of Mexico Sentinel Site Cooperative (Cooperative) developed and implemented an end-user driven process for tool creation. Research has suggested that integrating target end-users throughout tool development improves the probability a tool will be utilized, yet there is little practical guidance available on how to successfully design and implement an end-user driven tool development process. In this study, an end-user driven process and results from implementing the process during tool development are presented. Challenges, successful approaches, and lessons learned to support future tool development, especially for tools focused on sharing climate science are identified. Guidance is provided on needed expertise, timelines for engagement with target end-users, and methods on how to solicit, analyze, and assimilate end-user needs, perspectives, and priorities into a final product.